Investigation of photosensitivity side effect of systemic doxycycline used in the treatment of acne vulgaris - Sabir Hasanbeyzade; Demirci Saadet, Elif (Journal of Pakistan Association of Dermatologists, 2023)
Objective In this study, photosensitivity and other side effects due to the usage of systemic doxycycline in summer during acne treatment and whether these side effects were related to the demographic and clinical properties of the patients were investigated. Â Methods Before conducting the study, approval of the ethics committee of the hospital was obtained. 251 patients who applied to the dermatology outpatient clinic between 01.05.2021-30.09.2021 and were diagnosed with moderate-severe acne were included in the study. Demographic characteristic of the patients, clinical and treatment features, and development of photosensitivity or other side effects during or after the treatment were examined. Â Results Â Side effects were seen in 9 out of a total of 251 patients (3.6%). Among these patients, 5 patients (2%) had erythematous papules or plaque-like lesions on the face, and 4 patients (1.6%) had erythematous papules on the forearms. A statistically significant difference for age, sex, the severity of the disease, and treatment dose was not detected between groups classified according to the side effects (p values were respectively: 0.67, 0.058, 0.343, and 0.858). Statistically, a significant difference was found between these groups for the treatment period and usage of sun protection (p values were respectively: 0.011 and 0.003). Â Conclusion In patients who have erythematous papules and plaques on the face, these findings regressed with topical treatment. Therefore these findings were considered to be due to the usage of the topical acne agent.Â However, most patients having erythematous papules on their forearms were not using sunscreens and had personal and/or familial history of atopy. Because side effects did not require cessation of the systemic treatment and regressed with administered treatment; in the case of regular usage of sunscreen and utilization of benzoyl peroxide in combination, the photosensitivity side effect was thought to be minimal. Â